1993
DOI: 10.1159/000113821
|View full text |Cite
|
Sign up to set email alerts
|

Sound Detection and Processing by Fish: Critical Review and Major Research Questions (Part 1 of 2)

Abstract: The literature on fish hearing has increased significantly since our last critical review in 1973. The purpose of the current paper is to review the more recent literature and to identify those questions that need to be asked to develop a fuller understanding of the auditory capabilities and processing mechanisms of fishes. We conclude that while our understanding of fish hearing has increased substantially in the past years, there are still major gaps in what we know. In particular, the comparative functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
194
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(198 citation statements)
references
References 138 publications
1
194
0
3
Order By: Relevance
“…Stimulus amplitudes were then adjusted in MATLAB so that relative sound pressures across all frequencies (75-385Hz) were within a ±1dB window. Although all calibrations and data are reported as measures of pressure, previous studies have shown that the midshipman peripheral auditory system is primarily sensitive to particle motion and not pressure (Weeg et al, 2002), like many other fishes that lack specialized adaptations for pressure detection (Popper and Fay, 1993). Despite their sensitivity to particle motion, midshipman auditory afferents respond similarly to both iso-pressure stimuli from sound sources such as those used in the present study and vertical acceleration (Weeg et al, 2002).…”
Section: Stimulus Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulus amplitudes were then adjusted in MATLAB so that relative sound pressures across all frequencies (75-385Hz) were within a ±1dB window. Although all calibrations and data are reported as measures of pressure, previous studies have shown that the midshipman peripheral auditory system is primarily sensitive to particle motion and not pressure (Weeg et al, 2002), like many other fishes that lack specialized adaptations for pressure detection (Popper and Fay, 1993). Despite their sensitivity to particle motion, midshipman auditory afferents respond similarly to both iso-pressure stimuli from sound sources such as those used in the present study and vertical acceleration (Weeg et al, 2002).…”
Section: Stimulus Generationmentioning
confidence: 99%
“…We have investigated peripheral auditory plasticity in a teleost fish, the plainfin midshipman (Porichthys notatus Girard 1854; family Batrachoididae), that shows seasonal, reproductive state-dependent plasticity in the ability to encode the upper harmonics of vocalizations (Fig.1A,B). As females shift from a non-reproductive to a reproductive state, they exhibit a steroid-dependent improvement in frequency encoding by eighth nerve afferents to the saccule (Sisneros and Bass, 2003;Sisneros et al, 2004a), the main auditory division of the inner ear in midshipman and most teleosts (Fig.1C insert) (McKibben and Bass, 1999;Popper and Fay, 1993). We tested the hypothesis that this plasticity is not sex dependent, with males also exhibiting concurrent shifts in plasma steroid levels and auditory encoding as reflected in frequency sensitivity of the hair cell epithelium of the saccule.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous white noise of 110 and 130 dB L Leq significantly influenced auditory thresholds in both otophysine species, whereas in L. gibbosus the 110 dB noise did not shift hearing thresholds; only the 130 dB noise level evoked a smaller (as compared to the otophysines) loss in auditory sensitivity. Hearing generalists such as sunfish are generally less sensitive to sounds than hearing specialists (i.e., otophysines; Hawkins and Myrberg 1983;Popper and Fay 1993;Ladich and Popper, 2004). In our experiments, the spectrum level of the lower noise lies at least 25 dB below the hearing thresholds so that the noise has no masking effect.…”
Section: Differential Effects Of Background Noise On Hearing Sensitivitymentioning
confidence: 99%
“…It has been proposed that the inner ear of otophysans can be stimulated by particle motion via the direct pathway and by sound pressure via the indirect pathway, i.e., the swim bladder and the Weberian ossicles (see Popper and Fay 1993;Lu 2004 for reviews). The swim bladder in zebrafish starts to inflate at 5 dpf but the Weberian ossicles do not exist for zebrafish younger than 1 week old (Higgs et al 2003;Grande and Young 2004).…”
Section: Introductionmentioning
confidence: 99%